Age of information foundations and applications - Abd-Elmagid, Mohamed A.; Dhillon, Harpreet S.; Pappas, Nikolaos; Saad, Walid; Zhou, Bo (Cambridge University Press, 2023)
A comprehensive treatment of a crucial tool, this text provides detailed exposition of the communication and network theoretic foundations of Age of Information. It includes extensive real-world applications including caching, the Internet of Things, and energy harvesting networks, making this a vital resource for graduate students and researchers.